Learning from the Past : India Uttar Pradesh Sodic Lands Reclamation Project - Kuehnast, Kathleen (World Bank, Washington, DC, 2012)
India's Uttar Pradesh Sodic Lands Reclamation Project has two objectives. First, it seeks to reverse the decline of productivity through sustainable reclamation of sodic lands. Second, it is intended to prevent additional increases in sodicity through strengthening local institutions and enabling effective management of such programs with strong beneficiary participation and nongovernmental organization (NGO) support. This objective contributes to the alleviation of poverty of families managing sodic lands. Social Development best practices elements were identified as using: multi-dimensional approach to poverty reduction aimed at enhancing opportunities, capabilities, empowerment, and security of the poor; institutionalized mechanisms for participation and decentralized implementation; and ongoing monitoring and evaluation of social development outcomes by the government and community. Lessons learned focused on establishing the correct sequence of project activities is a key ingredient of success. In this case, the sequence involved first establishing property rights and land titling, then creating organizations of the poor, and then providing technical solutions and resources for implementation. Transparency and participatory problem-solving by stakeholders builds ownership. Investment in organizational development and local capacity building lays the groundwork for decentralized management by beneficiaries.